The Relations Of Regional Original Income And Balanced Funds On Financial Performance: Empirical Study Of Districts And Cities In Central Java 2019-2021 - Yulita Setiawanta (Fakultas Ekonomi dan Bisnis Universitas Dian Nuswantoro, 2024)
The purpose of this study was to determine the effect of (PAD) regional original income and balance funds on the financial performance of district and city governments in Central Java Province. The population used in this study are districts or cities throughout Central Java Province with a total of 36. The sampling method used is purposive sampling. This study uses secondary data in the form of a APBD realization report for the 2019-2021 fiscal year. The data analysis method used is multiple linear regression analysis. Based on the results of the research conducted, it can be seen that regional original income does not have a significant effect on financial performance, while balancing funds have a significant effect on the financial performance of district and city governments in Central Java Province.